2012
DOI: 10.1007/s11940-012-0176-7
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Compression

Abstract: Spinal cord disease represents a major cause of morbidity and suffering in cancer patients. Prevention or minimization of neurologic deficits depends on an understanding of early symptoms, clinical course, and treatment options. Early diagnosis is crucial, as current treatments usually arrest the course of the disease but much less commonly restore lost neurologic function. This article will review the epidemiology, pathophysiology, symptomatology, diagnosis, and management of the causes of spinal cord dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 115 publications
(93 reference statements)
0
31
0
Order By: Relevance
“…2-9 The strongest predictor of neurologic outcome with treatment is the neurologic status when treatment is initiated. 10 A large, well designed German retrospective cohort study found an association between slower development of motor deficits before the start of radiotherapy and a better functional outcome after treatment. 11…”
Section: Motor Deficitmentioning
confidence: 99%
See 2 more Smart Citations
“…2-9 The strongest predictor of neurologic outcome with treatment is the neurologic status when treatment is initiated. 10 A large, well designed German retrospective cohort study found an association between slower development of motor deficits before the start of radiotherapy and a better functional outcome after treatment. 11…”
Section: Motor Deficitmentioning
confidence: 99%
“…15 It also improves outcomes (including reducing local recurrence rates) after surgery and in patients who are not surgical candidates. 10 There are three goals of treatment with radiotherapy:…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with spinal instability have a better neurological outcome with tumour resection and surgical stabilisation prior to radiotherapy. 19 …”
Section: Introductionmentioning
confidence: 99%
“…Some authors state a minimum of 3-month life expectancy to consider operative treatment 5 , and others extend this limit to about 6 months 4,6 . Therefore, predicting survival is the key factor in selecting the proper treatment modality 6,7 .…”
mentioning
confidence: 99%